Relation between the dimensions and intraluminal pressure of the pharyngoesophageal segment and tracheoesophageal voice and speech proficiency. Issue 4 (20th January 2012) - Takeshita, Telma Kioko; Zozolotto, Henrique Ceretta; Ribeiro, Eduardo Alvarez; Ricz, Hilton; de Azevedo‐Marques, Paulo Mazzoncini; Dantas, Roberto Oliveira; Aguiar‐Ricz, Lílian
Abstract Background The objective of the present study was to relate the dimensions and the intraluminal pressure of the pharyngoesophageal segment (PES) to the voice and speech proficiency of total laryngectomees with a tracheoesophageal prosthesis (TEP). Methods Twenty total laryngectomees with secondary TEP insertion underwent evaluation of voice and speech, manometry, and videofluoroscopy. Results Most laryngectomees (65%) were moderate speakers. The poorer speakers presented a lower intraluminal pressure in the PES at rest (4.44 mmHg) and a higher value (40.46 mmHg) during phonation. Good speakers presented a significant difference in the anteroposterior distance between prominence of the PES and the posterior pharyngeal wall (PPES‐PPW) in the rest (6.09 mm) to phonation (3.24 mm). Conclusions The poorer speakers presented a lower intraluminal pressure in the PES at rest and a higher value during phonation compared with moderate speakers. Good speakers showed a significant difference in the PPES‐PPW dimension. © 2012 Wiley Periodicals, Inc. Head Neck, 2013